فاعلية الاتصال الإلكتروني داخل المؤسسات الاقتصادية الجزائرية الاغواط - إيمان شلالي; د/عبد القادر علال (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: جاءت دراستنا بعنوان فاعلية الاتصال الإلكتروني داخل المؤسسات الاقتصادية الجزائرية – دراسة ميدانية بمديرية الصيانةDMLسونطراك بالاغواط. وانطلقتدراستنا من الإشكالية:-ما مدى فاعلية الاتصال الإلكتروني داخل مديرية الصيانة سوناطراك الاغواط DML؟ وتتفرع الإشكالية العامة للدراسة إلى مجموعة من التساؤلات الفرعية تتمثل في: 1- هل تعتمد مديرية الصيانة DML على الاتصال الإلكترونيفي عملها ؟ 2- هل يساهم استخدام التطبيقات الإليكترونية في تسهيل الاعمال الادارية والتواصل بين الموظفين داخل مؤسسة سوناطراك الاغواط؟ 3- فيما يتجلى تأثير استخدام التطبيقات الإلكترونية على مستوى أداء الموظفين ؟ نهدف من خلال دراستنا الى التعرف على فاعليةالاتصالالإلكترونيفيالمؤسسةالاقتصاديةالجزائرية، وفي دراستنا اعتمدنا على المنهج الوصفي وأداة جمع البيانات تمثلت في الاستبيان لدراسة مجتمع الدراسة المتكون من 300 عاملا بمؤسسة الاقتصادية مديرية الصيانة بالاغوطDMLحيث توصلنا الى النتائج التالية: 1. مؤسسة مديرية الصيانة DML بالأغواط تعتمد على عدة وسائل تساهم في تحسين فعاليات أداء عمالها الهاتف والبريد الإلكتروني، كما ان عمال مؤسسة المديرية يرون ان الاعتماد على وسائل الاتصال الإلكتروني تساهم في تسريع العملية الاتصالية كونها إلكترونية وجاءت من اجل التسريع في العملية الاتصالية . 2. وسائل الاتصال الإلكتروني هي الأكثر استخداما بالمؤسسة الاقتصادية مديرية الصيانة DMLبالأغواط من أجل ضمانوصول وتدفق المعلومات بكل سرعة وسهولة كما يكمن الاتصال الالكتروني من أرشفة الرسائل بين الطرفين كي تأخذ الطابع الرسمي. 3. مؤسسة DML بالأغواط دائما ما تعتمد على الاتصال في عملها وان كل عمالها يعرفون أهمية ودور الاتصال في المؤسسة كما تستخدم كل أنواع الاتصالات منها الأفقية والصاعدة والنازلة من اجل ضمان سيرورة العمل وتبادل المعلومات والخبرات. 4. العملية الاتصالية داخل المؤسسة الاقتصادية مديرية الصيانة بالأغواط تساعد العمال على أداءهم المهني بشكل جيد وعملي كما تساهم في تطوير العمل بشكل عام من خلال التواصل الدائم بين افراد المؤسسة. Study summary Our study entitled the effectiveness of electronic communication in the Algerian economic institution - a field study in the Directorate of Maintenance DML Sonatrach in Laghouat. Our study started from the problem: What is the extent of the impact of electronic communication on the effectiveness of communications within the Maintenance Directorate SonatrachLaghouat DML? The general problem of the study is divided into a set of sub-questions, as follows: 1) Does the DML Maintenance Directorate rely on electronic communication in its work? 2) Did the use of electronic applications contribute to facilitating administrative work and communication between employees within SonatrachLaghouat? 3) What is the impact of the use of electronic applications on the level of employee performance? We aim through our study to identify the effectiveness of electronic communication in the Algerian economic institution, and in our study we relied on the descriptive method and data collection tools. 1. The DML Maintenance Directorate Establishment in Laghouat relies on several means that contribute to improving the activities of the performance of its workers by phone and e-mail, and the workers of the Directorate Establishment believe that relying on electronic means of communication contributes to accelerating the communication process as it is electronic and came in order to speed up the communication process. 2. The means of electronic communication are the most widely used in the economic institution, Maintenance Directorate, DML, in Laghouat, in order to ensure the access and flow of information quickly and easily. Electronic communication also consists of archiving messages between the two parties to take on an official nature. 3. The DML Foundation in Laghouat has always relied on communication in its work, and all its workers know the importance and role of communication in the institution. It also uses all types of communications, including horizontal, upwards and downwards, in order to ensure the workflow and exchange of information and experiences. 4. The communication process within the economic institution, the Maintenance Directorate in Laghouat, helps the workers in their professional and practical performance, and also contributes to the development of the work in general through constant communication between the members of the institution.
دراسة ميدانية بمديرية الصيانة -DML- الاغواط